PENYALURAN KREDIT USAHA RAKYAT MIKRO TERHADAP MANAGIAH CATERING: Micro People's Business Credit Distribution to Managiah Catering - Gani, Muhammad Hasya; Abrianti, Sharda (Faculty of Law, Universitas Trisakti, 2025)
As financial intermediaries, banks act as a middleman between clients with insufficient funds and clients with surplus funds. One of the primary businesses of banks is credit. Credit agreements agreed upon by the Bank as Creditor and Debtor. Business owners, particularly micro, small, and medium-sized enterprises (UMKM), employ the distribution of funds to enhance revenue. The People's Business Credit Program (KUR) is one of the programs the government has adopted to assist. Managiah Catering requested a KUR loan under the Micro KUR program, but while the agreement is taking place, Managiah Catering suggested extra funding to boost production capital. PT Bank Rakyat Indonesia (Persero) Tbk (BRI Bank) turned down the submission due to the requirement that the prior loan be paid back in full. How is the implementation of Micro KUR distribution to Managiah Catering by BRI Bank? is the problem formulation in this article. This study is normative and descriptive in character. It employs qualitative data analysis and deductive conclusion-making The result of this study investigates the implementation of Micro KUR distribution, finding it in compliance with statutory regulations but contradicting Article 24 paragraph (1) of Coordinating Ministerial Decree No. 1 of 2023 related to extra funding.